Preparation method, product and application of hydrophilic PLA oil-water separation membrane

The PLA@PDA nanofiber membrane prepared and modified hydrophilically through electrospinning technology solves the problem of poor hydrophilicity of traditional PLA membranes, achieves efficient oil-water separation, and meets environmentally friendly and economical treatment needs.

CN119318892AInactive Publication Date: 2025-01-17BEIJING UNIV OF TECH

Patent Information

Application Number
CN202411606820.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional PLA membranes have poor hydrophilicity due to their hydrophobic functional groups, which are easily blocked by oil, resulting in low oil-water separation efficiency and difficult to effectively treat oil-containing wastewater in the emulsified oil state.

Method used

PLA nanofiber membrane is prepared by electrospinning technology, and immersed in dopamine hydrochloride solution for hydrophilic modification to form a super hydrophilic PLA@PDA nanofiber membrane, which improves its porosity and interface volume ratio and enhances the Separation ability of oil-water emulsion.

Benefits of technology

It has achieved efficient oil-water separation, with a separation efficiency of more than 98%, and has good separation effects on n-hexane, gasoline, petroleum ether and peanut oil. The membrane is biodegradable and low-cost, which is suitable for environmental protection needs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318892A_ABST
    Figure CN119318892A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of polymer oil-water separation membranes, in particular to a preparation method, a product and application of a hydrophilic PLA oil-water separation membrane. The preparation method of the hydrophilic PLA oil-water separation membrane comprises the following steps: dissolving polylactic acid in an organic solvent to obtain a spinning solution; carrying out electrostatic spinning on the spinning solution to prepare a PLA nanofiber membrane; the PLA nanofiber membrane is soaked in a dopamine hydrochloride solution, then membrane cloth is taken out, washed and dried, and the hydrophilic PLA oil-water separation membrane is obtained. The preparation method is low in cost and simple in preparation process. The PLA (at) PDA nanofiber membrane prepared by the preparation method disclosed by the invention is relatively high in oil-in-water emulsion separation efficiency and relatively high in separation rate, and has a good separation effect on n-hexane, gasoline, petroleum ether, peanut oil and the like, and the separation efficiency can reach 98% or above. The PLA (at) PDA nanofiber membrane disclosed by the invention is simple and convenient to apply and does not cause secondary pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer oil-water separation membrane preparation, and in particular to a preparation method, product and application of a hydrophilic PLA oil-water separation membrane. Background Art

[0002] Frequent oil spills and the wanton discharge of industrial oily wastewater pose a serious threat to freshwater resources, the ecological environment and human health. According to surveys and studies, approximately 3.2 billion cubic tons of oil enters the water body and forms oily wastewater every year worldwide. The oil in wastewater is divided into four states according to its physical state: free oil, dispersed oil, emulsified oil and dissolved oil. Among them, emulsified oil is extremely difficult to handle.

[0003] Traditional methods for treating oily wastewater, such as physical adsorption, chemical coagulation and microbial degradation, have problems such as low separation efficiency, high cost, secondary pollution or time-consuming. Membrane separation technology has become one of the most promising technologies in the field of oil-water separation in recent years due to its advantages such as simple operation, high efficiency, energy saving and economy. Membrane is a material with selective separation function. The process of using the selective separation of membrane to separate, purify and concentrate different components of the feed liquid is called membrane separation. The membrane separation method commonly used in the treatment of oily wastewater can be divided into superhydrophilic and superoleophobic membranes and superhydrophobic and superoleophilic membranes according to the surface properties of the membrane. The strength of hydrophilicity and hydrophobicity depends on the raw material and pore size of the membrane. Membrane materials with good hydrophilicity are not easily contaminated, and are easy to clean and restore even if the membrane pores are blocked.

[0004] Electrospinning is a membrane-making method that uses electrostatic action to spray polymer solutions into micro-nanoscale fibers. In addition, nanofiber membranes prepared by electrospinning have higher porosity and interface volume ratio than other types of polymer membranes, thus showing excellent prospects in the field of oil-water separation.

[0005] Polylactic acid (PLA) is a polymer biomass material synthesized from renewable plant resources such as corn and sugarcane, with excellent biodegradability and biocompatibility. Moreover, PLA membranes do not produce hazardous waste, and PLA can be degraded into lactic acid by specific microorganisms. In addition, PLA membranes are cheaper than polyvinylidene fluoride, polyethersulfone and other traditional membranes. Therefore, PLA membranes are ideal candidate materials for replacing traditional non-renewable petrochemical-based materials. However, PLA membranes have poor hydrophilicity due to their hydrophobic functional groups such as methyl and ester groups. When separating oil-water emulsions, the membrane pores are easily blocked by oil, resulting in a decrease in membrane flux. Therefore, it is of great significance to develop a super-hydrophilic and super-oleophobic PLA oil-water separation membrane. Summary of the invention

[0006] Based on the above content, the present invention provides a preparation method, product and application of a hydrophilic PLA oil-water separation membrane.

[0007] To achieve the above object, the present invention provides the following solutions:

[0008] One of the technical solutions of the present invention is a method for preparing a hydrophilic PLA oil-water separation membrane, comprising the following steps:

[0009] Dissolving polylactic acid in an organic solvent to obtain a spinning solution;

[0010] Electrospinning the spinning solution to obtain a PLA nanofiber membrane;

[0011] The PLA nanofiber membrane is immersed in a dopamine hydrochloride solution, and then the membrane cloth is taken out, washed, and dried to obtain the hydrophilic PLA oil-water separation membrane.

[0012] The second technical solution of the present invention is a hydrophilic PLA oil-water separation membrane prepared according to the above-mentioned preparation method.

[0013] The third technical solution of the present invention is the application of the above-mentioned hydrophilic PLA oil-water separation membrane in the treatment of oily wastewater.

[0014] The present invention discloses the following technical effects:

[0015] 1. The hydrophilic PLA oil-water separation membrane (PLA@PDA nanofiber membrane) prepared by the present invention using electrospinning technology not only has the high strength of polylactic acid, but is also biodegradable and meets environmental protection requirements, and has a high porosity and specific surface area. The preparation method of the present invention has low cost and simple manufacturing process.

[0016] 2. PLA is hydrophobic in nature, so it can be hydrophilically modified using PDA to obtain a super-hydrophilic PLA nanofiber membrane. The prepared super-hydrophilic PLA@PDA nanofiber membrane can be used in the field of oil-water separation.

[0017] 3. The PLA@PDA nanofiber membrane prepared by the present invention has a high separation efficiency for water-in-oil emulsions and a fast separation rate, and has a good separation effect on n-hexane, gasoline, petroleum ether and peanut oil, and the separation efficiency can reach more than 98%. The PLA@PDA nanofiber membrane of the present invention is easy to use and will not cause secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1Schematic diagram of the chemical reaction occurring during the preparation of PLA@PDA nanofiber membranes in the present invention.

[0020] Figure 2 These are actual photos of the PLA nanofiber membrane and PLA@PDA nanofiber membrane prepared in Example 1 of the present invention.

[0021] Figure 3 This is a fiber diameter distribution diagram of the PLA nanofiber membrane prepared in Example 1 of the present invention.

[0022] Figure 4 This is a diagram showing the separation effect of the PLA@PDA nanofiber membrane prepared in Example 4 of the present invention on oil-in-water emulsion.

[0023] Figure 5 This is a diagram showing the separation efficiency of the PLA@PDA nanofiber membrane prepared in Examples 1-4 of the present invention for oil-in-water emulsions.

[0024] Figure 6 This is a diagram showing the wetting behavior of the PLA nanofiber membrane prepared in Example 1 of the present invention and the PLA@PDA nanofiber membrane prepared in Examples 1-4 to water.

[0025] Figure 7 This is a diagram showing the separation efficiency of the PLA@PDA nanofiber membrane prepared in Example 4 of the present invention for four simulated oil-in-water emulsions: n-hexane, gasoline, petroleum ether and peanut oil.

[0026] Figure 8 This is a diagram of the separation efficiency of the PLA@PDA nanofiber membrane prepared in Example 4 of the present invention for 30 separation cycles of oil-in-water emulsion. DETAILED DESCRIPTION

[0027] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0028] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0029] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0030] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0032] Polydopamine (PDA) contains a large number of hydrophilic functional groups such as hydroxyl, amino and catechol groups in its molecular structure, which can effectively improve the hydrophilicity and hydrophobicity of the material surface. The development of a super-hydrophilic and super-oleophobic separation membrane prepared by covalently linking the functional groups in the PDA and PLA molecular chains is expected to replace the traditional difficult-to-degrade polymer membranes and contribute to resource conservation and environmental protection.

[0033] The first aspect of the present invention provides a method for preparing a hydrophilic PLA oil-water separation membrane, comprising the following steps:

[0034] Dissolving polylactic acid in an organic solvent to obtain a spinning solution;

[0035] Electrospinning the spinning solution to obtain a PLA nanofiber membrane;

[0036] The PLA nanofiber membrane is immersed in a dopamine hydrochloride solution, and then the membrane cloth is taken out, washed, and dried to obtain the hydrophilic PLA oil-water separation membrane.

[0037] In some embodiments of the present invention, the mass volume ratio of the polylactic acid to the organic solvent is 1 g:9 mL.

[0038] In some embodiments of the present invention, the organic solvent is a mixture of dichloromethane and N,N-dimethylformamide in a volume ratio of 4:1.

[0039] The refinement of fiber diameter is the result of the combined effects of solution viscosity, electric field strength, surface tension and solvent volatility. PLA is easily soluble in dichloromethane, and the addition of N,N-dimethylformamide can obtain electrospun fibers with smaller fiber diameters due to its higher dielectric constant and conductivity. The above-mentioned volume ratio of dichloromethane to N,N-dimethylformamide of 4:1 can obtain a spinning solution with the best solution viscosity and surface tension.

[0040] In some embodiments of the present invention, the polylactic acid is fully dissolved in the organic solvent by magnetic stirring for 12 hours.

[0041] In some embodiments of the present invention, the electrospinning parameters are set as follows: the spinning solution ejection rate is 1.0 mL / h, the external electric field is 22 kV, the drum collector speed is 200 rpm, the distance between the receiver and the needle tip is 15 cm, the temperature is 25±2°C, and the humidity is 40±5%.

[0042] In some embodiments of the present invention, the electrospinning further comprises a step of drying at 40° C. for 24 hours.

[0043] In some embodiments of the present invention, the dopamine hydrochloride solution is prepared by dissolving dopamine hydrochloride in tris(hydroxymethylaminomethane) hydrochloride buffer; the mass concentration of the dopamine hydrochloride solution is 0.25%-1.0% and the pH of the dopamine hydrochloride solution is 8.5.

[0044] The present invention utilizes polydopamine to covalently connect with PLA to modify the hydrophilicity of the PLA nanofiber membrane.

[0045] In some embodiments of the present invention, the immersion time is 24 hours.

[0046] In some embodiments of the present invention, stirring is also performed during the immersion process.

[0047] In some embodiments of the present invention, before immersing the PLA nanofiber membrane in the dopamine hydrochloride solution, the step of wetting the PLA nanofiber membrane with ethanol is also included.

[0048] In some embodiments of the present invention, the drying temperature is 40°C.

[0049] The second aspect of the present invention provides a hydrophilic PLA oil-water separation membrane prepared according to the above preparation method.

[0050] The hydrophilic PLA oil-water separation membrane has the characteristics of high specific surface area, high porosity, and nanometer fiber diameter. The hydrophilic PLA oil-water separation membrane has a high separation efficiency for water-in-oil emulsions, and maintains a stable separation effect after being recycled ten times. More importantly, the waste membrane cloth is completely biodegradable and meets environmental protection requirements. It can be seen that the hydrophilic PLA oil-water separation membrane has a wide range of applications.

[0051] The third aspect of the present invention provides an application of the hydrophilic PLA oil-water separation membrane in the treatment of oily wastewater.

[0052] The present invention uses electrostatic spinning to prepare a PLA oil-water separation membrane (hydrophobicity), and selects the best modified PLA oil-water separation membrane (hydrophilicity) by adjusting different mass fractions (0.25%, 0.5%, 0.75%, 1.0%) of dopamine hydrochloride solution to achieve a higher oil-water separation efficiency. The super-hydrophilic PLA membrane prepared by the method has the characteristics of high specific surface area, high porosity, biodegradability and environmental friendliness, and has a high separation efficiency and a fast separation rate for oil-in-water emulsions.

[0053] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.

[0054] The technical solution provided by the present invention is described in detail below in conjunction with the examples, but they should not be understood as limiting the scope of protection of the present invention. In the following examples, unless otherwise specified, the data obtained are the average values ​​of more than three repeated tests.

[0055] Example 1: Preparation of PLA@PDA nanofiber membrane

[0056] Step 1, preparation of PLA nanofiber membrane: add 2g of polylactic acid pellets to a mixed solution of 14.4mL of dichloromethane and 3.6mL of N,N-dimethylformamide. After magnetic stirring for 12h, the spinning solution is obtained. The spinning solution is injected into the electrospinning equipment and electrospun under the conditions of a spinning solution ejection rate of 1.0mL / h, an external electric field of 22kv, a drum collector speed of 200rpm, a distance between the receiver and the needle tip of 15cm, a temperature of 25±2℃, and a humidity of 40±5%. Then, it is dried in an oven at 40℃ for 24h and peeled off to obtain the PLA nanofiber membrane. Figure 3 Figure 3 is the diameter distribution diagram of PLA fibers. The fiber diameter in the nanofiber membrane is distributed in the range of (4.60±1.23) μm. After being treated with dopamine hydrochloride, dopamine adheres to the surface of the fiber diameter, but has little effect on the diameter. Therefore, only the original PLA nanofiber membrane is selected as the research object.

[0057] Step 2, hydrophilic modification of the PLA nanofiber membrane: 0.25g of dopamine hydrochloride is dissolved in 100mL of tris(hydroxymethylaminomethane) hydrochloride buffer to obtain a dopamine hydrochloride solution with a mass concentration of 0.25%. Since dopamine will decompose or inactivate when the pH value is too low or too high, the pH of the dopamine hydrochloride solution is adjusted to 8.5 to ensure the smooth self-polymerization reaction of dopamine. Subsequently, the PLA nanofiber membrane is moistened with ethanol and immersed in the prepared dopamine hydrochloride solution and stirred for 24 hours. Take out the membrane cloth and wash it thoroughly with deionized water and ethanol twice. After drying in an oven at 40°C, a modified PLA nanofiber membrane, namely PLA@PDA nanofiber membrane (marked as 0.25% PLA@PDA) is obtained.

[0058] Example 2: Preparation of PLA@PDA nanofiber membrane

[0059] The only difference from Example 1 is that the mass concentration of the dopamine hydrochloride solution in step 2 is 0.5%, and the remaining steps and parameters are the same as those in Example 1. The prepared PLA@PDA nanofiber membrane is marked as 0.5% PLA@PDA.

[0060] Example 3: Preparation of PLA@PDA nanofiber membrane

[0061] The only difference from Example 1 is that the mass concentration of the dopamine hydrochloride solution in step 2 is 0.75%, and the remaining steps and parameters are the same as those in Example 1. The prepared PLA@PDA nanofiber membrane is marked as 0.75% PLA@PDA.

[0062] Example 4: Preparation of PLA@PDA nanofiber membrane

[0063] The only difference from Example 1 is that the mass concentration of the dopamine hydrochloride solution in step 2 is 1.0%, and the remaining steps and parameters are the same as those in Example 1. The prepared PLA@PDA nanofiber membrane is marked as 1.0% PLA@PDA. Figure 6 From the analysis of wettability behavior, the water contact angles of 0.75% PLA@PDA and 1.0% PLA@PDA both dropped to 0° within 1 s, showing superhydrophilicity. It is of little significance to continue to increase the mass concentration of dopamine hydrochloride solution.

[0064] Example 5: Separation efficiency of PLA@PDA nanofiber membranes prepared in Examples 1-4 at different mass concentrations of dopamine hydrochloride solution for oil-in-water emulsions

[0065] Preparation of water-in-oil emulsion: 1 mL of n-hexane was added to 99 mL of deionized water, and then 0.1 g of sodium dodecyl sulfate was added. After ultrasonication for 30 min, the water-in-oil emulsion stabilized by surfactant was obtained by vigorous stirring for 12 h.

[0066] PLA@PDA nanofiber membranes prepared at different dopamine hydrochloride solution mass concentrations were placed in a gravity-driven oil-water separation device, and 10 mL of the prepared water-in-oil emulsion was introduced into it. The oil content in the samples before and after filtration was extracted with petroleum ether, and the absorbance was measured by ultraviolet spectrophotometer, and the oil content in the water sample was calculated according to the standard curve.

[0067] The calculation method of separation efficiency is:

[0068] Wherein, C0 and C1 represent the oil contents in the emulsion before and after filtration, respectively.

[0069] Figure 4 This is a diagram showing the separation effect of the PLA@PDA nanofiber membrane prepared in Example 4 on the oil-in-water emulsion. It can be seen from the figure that the liquid is clear and transparent after filtration. Figure 5 ) It can also be seen that when the mass concentration of PDA is 0.25%, 0.5%, 0.75% and 1.0%, the separation efficiency of PLA@PDA nanofiber membrane for oil-in-water emulsion reaches 97.3%, 97.8%, 98.6% and 99.4% respectively. With the increase of PDA mass concentration, a large number of hydrophilic functional groups such as hydroxyl, amino and catechol groups make the fiber membrane more hydrophilic, thereby improving the separation efficiency of oil-in-water emulsion, and the separation efficiency is the highest when the mass concentration of PDA reaches 1.0%.

[0070] Example 6: Wetting behavior test of original PLA nanofiber membrane (i.e., PLA nanofiber membrane prepared in step 1 of Example 1) and PLA@PDA nanofiber membrane prepared in Examples 1-4 to water

[0071] The contact angles of the original PLA nanofibrous membrane and the PLA@PDA nanofibrous membrane prepared at different mass concentrations of dopamine hydrochloride solution were measured using a contact angle meter to evaluate the surface wettability of the nanofibrous membrane. Figure 6The water contact angle test diagram of the original PLA nanofiber membrane and the PLA@PDA nanofiber membrane prepared at different mass concentrations of dopamine hydrochloride solution under the conditions of Example 6. There is always a water droplet on the surface of the original PLA nanofiber membrane, and its shape remains unchanged after 10 minutes. The water contact angle is about 142.2°, which proves that the PLA nanofiber membrane has super hydrophobicity. Under the wrapping of hydrophilic PDA, the wettability of the PLA@PDA nanofiber membrane is reversed. As the mass concentration of dopamine hydrochloride solution increases from 0.25% to 1.0%, the PLA@PDA nanofiber membrane becomes more hydrophilic. When the mass concentration of dopamine hydrochloride solution is 0.5%, the water contact angle drops to 0° only in 5s; when the mass concentration of dopamine hydrochloride solution is 0.75% and 1.0%, the water contact angle drops completely to 0° within 1s. This fully proves that the modified PLA@PDA nanofiber membrane has super hydrophilicity.

[0072] Example 7: Separation efficiency of different types of oil-in-water emulsions prepared by the PLA@PDA nanofiber membrane in Example 4 at a dopamine hydrochloride solution concentration of 1.0%

[0073] The preparation and determination of the water-in-oil emulsion were the same as in Example 5, and the oils were n-hexane, gasoline, petroleum ether and peanut oil. Figure 7 It can be seen that the separation efficiency of PLA@PDA nanofiber membrane for four oil-in-water emulsions is above 99%, and the oil-water separation effect is good. Among them, the separation effect of PLA@PDA nanofiber membrane for petroleum ether in water emulsion reaches the highest of 99.5%. It can be seen that PLA@PDA nanofiber membrane has excellent performance in separating oil-in-water emulsions.

[0074] Example 8: Separation efficiency of PLA@PDA nanofiber membrane prepared in Example 4 at a dopamine hydrochloride solution concentration of 1.0% after 30 cycles

[0075] The preparation and determination of the oil-in-water emulsion were the same as in Example 5. Each time, 10 mL of the oil-in-water emulsion was introduced into the gravity-driven oil-water separation device for 30 cycles. The membrane was not rinsed at the end of each cycle. Figure 8 The separation effect of PLA@PDA nanofiber membrane on water-in-oil emulsion after 30 separation cycles. During the cyclic separation test using water-in-hexane emulsion, PLA@PDA nanofiber membrane showed excellent durability and recyclability. The separation ability of PLA@PDA nanofiber membrane for water-in-oil emulsion decayed very little in 30 cycles, and the separation efficiency remained above 94.45%.

[0076] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a hydrophilic PLA oil-water separation membrane, characterized in that: The following steps are involved: dissolving polylactic acid in an organic solvent to obtain a spinning solution; Electrospinning the spinning solution to obtain a PLA nanofiber membrane; The PLA nanofiber membrane is immersed in a dopamine hydrochloride solution, and then the membrane cloth is taken out, washed, and dried to obtain the hydrophilic PLA oil-water separation membrane.

2. The method for preparing the hydrophilic PLA oil-water separation membrane according to claim 1, characterized in that: The mass volume ratio of the polylactic acid to the organic solvent is 1 g:9 mL.

3. The method for preparing the hydrophilic PLA oil-water separation membrane according to claim 1, characterized in that: The organic solvent is a mixture of dichloromethane and N,N-dimethylformamide in a volume ratio of 4:

1.

4. The method for preparing a hydrophilic PLA oil-water separation membrane according to claim 1, characterized in that: The electrospinning parameters were set as follows: the spinning solution ejection rate was 1.0 mL / h, the applied electric field was 22 kV, the drum collector speed was 200 rpm, the distance between the receiver and the needle tip was 15 cm, the temperature was 25±2° C., and the humidity was 40±5%.

5. The method for preparing the hydrophilic PLA oil-water separation membrane according to claim 1, characterized in that: The dopamine hydrochloride solution is prepared by dissolving dopamine hydrochloride in tris(hydroxymethyl)aminomethane hydrochloride buffer solution; The mass concentration of the dopamine hydrochloride solution is 0.25%-1.0%.

6. The method for preparing the hydrophilic PLA oil-water separation membrane according to claim 1, characterized in that: The immersion time is 24 hours.

7. The method for preparing a hydrophilic PLA oil-water separation membrane according to claim 1, characterized in that: The drying temperature is 40°C.

8. The hydrophilic PLA oil-water separation membrane prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the hydrophilic PLA oil-water separation membrane as claimed in claim 8 in the treatment of oily wastewater.

Citation Information

Patent Citations

  • Hydrophilic PLA oil-water separation membrane and preparation method thereof

    CN115467084A

  • Preparation method of waste biomass-based Janus oil-water separation membrane and application of waste biomass-based Janus oil-water separation membrane in emulsion separation

    CN116510533A

  • Preparation method of Janus cellulose membrane based on waste plastic and application of Janus cellulose membrane to emulsion separation

    CN116510540A

  • Preparation method of super-hydrophilic polylactic acid (PLA) fiber membrane for separating oil-in-water emulsion

    CN117947578A

  • Oil and water separation membrane

    US20230234002A1

Cited By

  • Preparation method of PTFE oil-water separation composite membrane

    CN120169178A

  • A method for preparing a PTFE oil-water separation composite membrane

    CN120169178B

  • Preparation method of PLA oil-water separation membrane with sandwich structure

    CN121244023A